(untitled) (Bangladesh Journal of Medicine, 2021)
Background: Autism Spectrum Disorder (ASD) is a neurobehavioral disorder for which till date, no pharmacological treatment has been proven effective. Some studies on complementary alternative medicines have shown neurobehavioral improvements among children diagnosed with ASD, notably with the administration of a combination of Vitamin B6 and Magnesium. Methods: This trial was designed to observe the effectiveness of a combination of Vitamin B6 and Magnesium in children with ASD with hyperactivity. One of the primary aim was to investigate any improvement among the six domains of ASD: general observation, cognition, emotion, social behavior, communication, and sensory deficits. Patients attending the outpatient department of the Institute of Pediatric Neurodisorder and Autism (IPNA), Bangabandhu Sheikh Mujib Medical University, diagnosed as ASD, were selected for this trial on meeting the selection criteria diagnosed by DSM 5 (Diagnostic and Statistical manual of Mental disorders) and ADCL (Autism Diagnostic CheckList). Then the patients were randomly assigned into intervention group (Vitamin B6 and Magnesium) or placebo group. The intervention group received tablets of Vitamin B6 and Magnesium daily, for 3 months, where the dosage was pre-determined by age of the subjects. Patients aged 2-3 years received 50mg Magnesium and 25mg Vitamin B6 daily, aged 4-8 years received 100mg Magnesium and 50mg Vitamin B6 daily, and patients aged 9-12 years were given 200mg Magnesium and 100mg Vitamin B6 daily. The placebo group received similar looking oral placebo tablets for the duration as the intervention group. After 3 months, each patient was assessed once again using ADCL tool by a psychologist. Results: Seventy (70) patients were enrolled for this study over a period of seven months. Among them fifty (50) met all criteria to be eligible for analysis. Therefore, intention to treat (ITT) was seventy (70) and per protocol treatment was fifty (50). Of these patients, twenty-seven (27) received Vitamin B6 and Magnesium and twenty-three (23) received placebo. The improvement observed in the proportion of patients in the intervention group (81%) was significantly (pd”0.05) higher compared to placebo (47%) group. This study revealed an overall improvement in the symptoms of autism along with improvements in specific domains e.g., Emotion (pd”0.01) and Cognition (pd” 0.05). Conclusion: Despite the small population size, this study demonstrated neurobehavioural improvement among children with ASD with hyperactivity and irritability. Consequently, this can be expected that future studies conducted on a larger scale might help to establish the beneficial role of Vitamin B6 and Magnesium as a complementary treatment for autism with hyperactivity and irritability. Bangladesh J Medicine January 2021; 32(1) : 12-18